Dimensional heterostructures of 1D CdS/2D ZnIn2S4 composited with 2D graphene: designed synthesis and superior photocatalytic performance. Issue 9 (7th February 2017) - Tian, Qingyong; Wu, Wei; Liu, Jun; Wu, Zhaohui; Yao, Weijing; Ding, Jin; Jiang, Changzhong
Abstract : Multidimensional heterostructure of 1D/2D CdS/ZnIn2 S4 with 2D RGO are successfully synthesized, which exhibit superior photoactivity and good stability for the degradation of organic dyes. Abstract : The development of photocatalysts with superior photoactivity and stability for the degradation of organic dyes is very important for environmental remediation. In this study, we have presented a multidimensional (1D and 2D) structured CdS/ZnIn2 S4 /RGO photocatalyst with superior photocatalytic performance. The CdS/ZnIn2 S4 helical dimensional heterostructures (DHS) were prepared via a facile solvothermal synthesis method to facilitate the epitaxial growth of 2D ZnIn2 S4 nanosheets on 1D CdS nanowires. Ultrathin 2D ZnIn2 S4 nanosheets have grown uniformly and perpendicular to the surface of 1D CdS nanowires. The as-obtained 1D/2D CdS/ZnIn2 S4 helical DHS show good photocatalytic properties for malachite green (MG). Subsequently, 2D reduced graphene oxide (RGO) was introduced into the 1D/2D CdS/ZnIn2 S4 helical DHS as a co-catalyst. The photoactivity and stability of the CdS/ZnIn2 S4 /RGO composites are significantly improved after 6 cycles. The enhanced photoactivity can be attributed to the high surface area of RGO, the improved adsorption of organic dyes and the efficient spatial separation of photo-induced charge carriers. The transfer of photo-generated electrons from the interface of CdS and ZnIn2 S4 to RGO also restricted the photocorrosion of metal sulfide, suggesting an improved stability of the reused CdS/ZnIn2 S4 /RGO composited photocatalyst.